PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT OF ADAPTIVE PHYSICAL EDUCATION AND SPORTS ACTIVITIES - BARCHENKO S.A. («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
The article examines the problem of psychological and pedagogical support for individuals with disabilities, aimed at revealing their psychophysical potential and achieving high results through the optimization of the educational and training process using psychological methods of preparation.